Vocational Handicraft Activities in Improving Academic Achievement of Students with Deafblindness - Novianti, Ranti; Muhammad, Alfin Nur; Halimah, Halimah (Proceedings Series of Educational Studies, 2024)
This research aims to explore vocational activities in the form of handicrafts carried out by students with disabilities. Students with disabilities often face various challenges in the educational environment. Therefore, non-academic skills are needed to support their achievements in education. One type of non-academic ability in question is to train the skills possessed by students. This research uses a qualitative method with a case study approach to understand the dynamics involved. Data were collected through in-depth interviews with teachers and students. The results showed that the improvement of motoric and cognitive skills of students with disabilities significantly correlated with the improvement of their academic achievement. In addition, ongoing support from the family and school environment was also found to be an important factor in strengthening these skills. Based onthese findings, the researcher suggests that special education providers are consistent in developing the individual skills of students with disabilities to optimize their academic potential. The findings are expected to provide insights for educators and policy makers in designing more inclusive and effective education strategies for students with special needs. Keywords: Tunagrahita; Skills; Academic